The CT-Element of The C-Myc Gene Does Not Predispose to Chromosomal Breakpoints in Burkitt'S Lymphoma - Achim Weber; Marina I. Gutierrez; David Levens (Cellular Oncology)
Background: Chromosomal translocations are causally related to the development of many tumors. In Burkitt's lymphoma, abnormalities involving the c-myc gene are essential. The CT-element of the c-myc promoter adopts non-B-conformation in vivo and in vitro, and therefore provides a potential fragile site. Methods: We have developed a LM-PCR-based approach to test if chromosomal breakpoints indeed cluster in this region. Results: Amplifying both, wild-type as well as the translocated c-myc gene by LM-PCR, it was shown that chromosomal breakpoints did not cluster within the CT-element. Conclusions: Therefore, the CT-element is not especially susceptible to the formation of breakpoints leading to chromosomal translocations in Burkitt's lymphoma.